The archival records on Chinese slaves, convicts, exiles and ‘free blacks' at the Cape of Good Hope (1654 -1838): Conceptualising a digital curation project - Chen, Vanessa (Department of Knowledge and Information Stewardship, 2022)
Despite the growth of digital archives, there is no dedicated repository that systematically compiles the history of Chinese migration to South Africa. This qualitative study used 62 archival records housed at the Western Cape Archives and Records Service, to explore how the application of digital curation (particularly digitisation of materials) can be used in presenting, preserving and sharing the history on the first wave of Chinese slaves, convicts, exiles and ‘free blacks' at the Cape of Good Hope (1654 -1838). The study method consisted of three parts. First, a thorough literature search and understanding on the theoretical, practical and technical components of the subject. Second, the systematic collection and analyses of archival records (through a customised document analysis form) and third, an exploration on what digital curation can offer in terms of facilitating the access to and the preservation of these records. The study exists under a relativist paradigm which believes that reality is a product of power relations. It was found that the records provide valuable insight into the Cape's political development (from Dutch to British rule) and social hierarchies between Chinese individuals at the time. The archival content, being of historical significance, is in fact at a risk of physical and epistemological loss. This loss can be addressed through the application of digital curation which this study explores conceptually from the conception of a digital project to the use, reuse and dissemination of digital surrogates. It is hoped that this study can be used as a foundation or framework for refiguring the colonial archive and bringing other neglected South African histories to the forefront.